Effects of Psychoeducational Interventions Using Mobile Apps and Mobile-Based Online Group Discussions on Anxiety and Self-Esteem in Women With Breast Cancer: Randomized Controlled Trial - Ghanbari, Elaheh; Yektatalab, Shahrzad; Mehrabi, Manoosh (JMIR mHealth and uHealth, 2021)
Psychoeducation has turned into an effective tool in taking care of cancer patients and improving their psychophysical symptoms and quality of life. Despite the growing use of mobile phone apps in medical settings for improving health, evidence supporting their effectiveness in the psychoeducation of patients with breast cancer is rarely available. This study was conducted to investigate the effect of psychoeducational interventions on anxiety and self-esteem in women with breast cancer using a mobile app and an online support group. An unblinded randomized controlled trial based on mobile phones was conducted in Shiraz, Iran. A research assistant recruited 82 women with nonmetastatic breast cancer aged 20 to 60 years were from clinics during a face-to-face visit at the point of care and randomly assigned to an intervention group (n=41) and a wait-list control group (n=41) through blocked randomization. The intervention group received psychoeducational interventions through a mobile phone app and participated in nurse-assisted online mobile support sessions for a total four weeks, whereas the control group was put on a waiting list. The State-Trait Anxiety Inventory (STAI) and the Rosenberg Self-Esteem Scale (RSES) were used to measure the levels of anxiety and self-esteem as the main outcomes at baseline and one week after the intervention. A total of 82 patients with a mean age of 46.45 (SD 9.29) years recruited in Winter 2016 were randomly assigned to a wait-list control group (n=41) and intervention group (n=41). Five patients dropped out for different reasons. Comparing the postintervention mean scores of anxiety and its subscales using the independent t test showed statistically significant differences between the mobile psychoeducation group and controls (P<.001). The paired t test used to compare the postintervention mean scores of anxiety with its preintervention scores in the intervention group showed significant reductions in the scores of anxiety (95% CI -17.44 to -8.90, P<.001, d=1.02) and its two subscales (state anxiety: 95% CI -9.20 to -4.21, P<.001, d=0.88 and trait anxiety: 95% CI -8.50 to -4.12, P<.001, d=0.94). Comparing the postintervention mean scores of self-esteem showed statistically insignificant differences between the control and intervention groups (16.87 vs 17.97, P=.24). In contrast with the controls, using the paired t test showed that the increase in the postintervention mean scores of self-esteem were statistically significant in the intervention group compared with the preintervention scores (mean difference 2.05, 95% CI 1.28 to 2.82, P<.001). This study demonstrated the key role of mobile apps in decreasing anxiety and improving self-esteem in women with breast cancer through psychoeducational interventions. Similar studies with longer follow-ups are recommended that be conducted in this context. Iranian Registry of Clinical Trials IRCT2015072123279N2; https://en.irct.ir/trial/19882.